Ekonomi Kreatif Di M-Bloc Space Jakarta Sebagai Kegiatan Wisata - Chairunissa, Salsabilla Putri; Bhaskara, Gde Indra (JURNAL DESTINASI PARIWISATA, 2023)
The term of creative economy is developed from the concept of creativity-based capital which has the potential to increase economic growth in a region. Creativity is considered having capability in driving business opportunities for small businesses through the development of souvenirs, folk festivals, and so on. Creative economy and the tourism sector are two things that influence and synergize with each other if managed properly. This study uses a qualitative method which aims to identify tourism in M-Bloc Space Jakarta through the creative economy. The type of data used is qualitative data with data collections carried out through observation, in-depth interviews, and documentaries. The data analysis used is descriptive qualitative analysis. The results of this study indicate that the creative economy at M-Bloc Space Jakarta consists of eight creative economy subsectors, namely advertising, art market, crafts, design, fashion, music, publishing and printing, and culinary. Creative Economy at M-Bloc Space Jakarta as a tourism activity consists of (3S) Something to do, Something to see, Something to buy. Keyword: ekonomi kreatif, kegiatan wisata, creative hub, m-bloc space Jakarta.